Impact of the textile mesh on the efficiency of TRM strengthening solutions to improve the infill walls out-of-plane behaviour - Furtado, André (2020)
Different retrofitting techniques have been developed and proposed to prevent the masonry infill walls (MIW) out-of-plane collapse. Many other authors confirmed that these types of elements are vulnerable when subjected to earthquake loadings, leading to several casualties and economic losses. Based on this, the present manuscript comprises an experimental campaign of flexure strength tests on small masonry walls to discuss the efficiency of textile-reinforced mortar (TRM) strengthening solutions to improve their out-of-plane behaviour. For this, eighteen flexural strength tests parallel to the horizontal bed joints were carried out. Nineteen masonry infill walls made with hollow clay horizontal brick, eight non-strengthened and the remaining ones strengthened with TRM. The tests were performed according to the EN 1052-2 standard. In this study, the effect of textile mesh (weak or strong) is analysed in parallel with the efficiency of the strengthening solutions. The results are presented and discussed in terms of force-displacement response parameters and damages observations. From the tests, it was observed that the TRM strengthening improved the flexural strength capacity up to 54% and the out-of-plane deformation ability about 7.18 times.